2018
DOI: 10.1108/bjm-09-2017-0279
|View full text |Cite
|
Sign up to set email alerts
|

When does motivation to learn reduce innovative behavior? An examination of mediated-moderation model

Abstract: Purpose The purpose of this paper is to test and explain the context where motivation to learn (MTL) reduces innovative behavior in the organizational context. Design/methodology/approach The authors used questionnaire survey to collect data in a field study. In order to test the moderating effect of transfer climate, MTL on the relationship between MTL and innovative behavior, a sample of 606 employees was analyzed to examine the theoretical expectation by using multiple regression and bootstrapping. Find… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 71 publications
(92 reference statements)
0
13
2
Order By: Relevance
“…Another definition finds that transformational leaders enhance student creativity by providing psychological empowerment, which increases employee motivation to learn [6]. Intrinsic motivation contributes to innovative work behavior because they feel controlled by their activities [7]. Most such leaders usually encourage to engage in innovative work behavior by providing a supportive environment [8].…”
Section: A Transformational Leadership 1) Definition Of Transformational Leadershipmentioning
confidence: 99%
See 1 more Smart Citation
“…Another definition finds that transformational leaders enhance student creativity by providing psychological empowerment, which increases employee motivation to learn [6]. Intrinsic motivation contributes to innovative work behavior because they feel controlled by their activities [7]. Most such leaders usually encourage to engage in innovative work behavior by providing a supportive environment [8].…”
Section: A Transformational Leadership 1) Definition Of Transformational Leadershipmentioning
confidence: 99%
“…Motivation to learn as a mediating factor of innovative work behavior It is said that "a continuous commitment to learning is central to innovation" [30]. Students to be involved or not involved in innovative behavior are influenced by their motivation to learn [7]. Motivation to learn refers to the desire of students to learn new knowledge or insights that encourage individuals to be creative and innovative in their work [31].…”
Section: Motivation To Learn 1) Definition Of Motivation To Learnmentioning
confidence: 99%
“…Innovation has been identified as a significant strategy and practice contributing to corporate competitiveness and survival (Amabile, Conti, Coon, Lazenby, & Herron, 1996;Kehoe & Tzabbar, 2015;Lin, Zeng, Liu, & Li, 2018;Lungeanu, Stern, & Zajac, 2016;Zhao, Cacciolatti, Lee, & Song, 2015;Yu, Zheng, Wang, Dai, & Yan, 2018;Zhou & Hoever, 2014). Operating in a comprehensive institutional and industrial environment, firms demonstrate diverse innovation performance affected by a range of factors, such as organizational structures, firm capabilities of absorbing/adopting new knowledge and adapting to institutional conditions, and external environment (Baron & Tang, 2011;Jansen, Den Bosch, & Volberda, 2006;Jiao, Koo, & Cui, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The work environment includes the workplace, facilities and work aids, cleanliness, lighting, tranquility, and work relationships between people in the place. Yu et al (2018) showed that motivation had a significant predictor to Innovative Work Behavior, where study showed that motivation was the main factor to affect the Innovative Work Behavior. The high conditions of employee work motivation are related to high level of Innovative Work Behavior.…”
Section: Work Environment Affects Innovative Work Behavior Through Momentioning
confidence: 99%
“…Veithzal (2006: 455) stated that motivation is an encouragement or enthusiasm that can change a person's attitude or behavior to achieve the desired goals. Yu et al (2018) showed that motivation was a significant predictor of Innovative Work Behavior. While stated that motivation become a mediation factor for Innovative Work Behavior.…”
Section: Introductionmentioning
confidence: 99%